Peran Empati di Keluarga Fatherless pada Anak Usia Dewasa Awal - Salsa Cantika Aster Budiani; Ratnaningrum Z.D; Fatihatul Lailiyah (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
This study aims to explore the phenomenon of fatherlessness in family communication patterns. Fatherlessness, which refers to the lack of a father’s role either physically or psychologically, has become a significant issue in Indonesia, which ranks third in the world for fatherlessness cases. In this research, a qualitative method with a case study approach is used. Data were collected through in-depth interviews with informants who have experienced fatherlessness. The findings of the study indicate that the absence of a father has a significant impact on family communication patterns. Children who experience fatherlessness tend to have problems in interpersonal communication, decision-making, and emotion management, highlighting the importance of empathy in fatherless families. These findings are expected to raise public awareness, especially among parents, about the importance of a father's presence in the family, and contribute to the development of communication studies related to the phenomenon of fatherlessness.